Normal Value of Thrombocytes Indices in Indonesian Adults: Focus on Gender and Ages - Usi Sukorini; Adika Zhulhi Arjana; Tri Ratnaningsih; Rahmat Dani Satria (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Monitoring platelet count and related indices is crucial for managing hematological disorders. No studies are reporting normal platelet indices in the adult Indonesian population. Therefore, this study was conducted to establish normal reference values for platelet count and indices in a healthy population in Indonesia and investigate their association with platelet count and each parameter.METHODS: This cross-sectional study included healthy adults from both sexes who underwent hematological testing in our laboratory. Two mL of venous blood was drawn and analyzed using an automated machine ADVIA 2120 to identify platelet count, mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT), mean platelet component (MPC), platelet component distribution width (PCDW), mean platelet mass (MPM), platelet mass distribution width (PMDW), and large platelet count.RESULTS: This study included 1037 subjects with median of 27 (18–58) years old. Normal reference range values for platelet indices in adult Indonesians was established, which was significantly different between males and females (p<0.05) in following parameters: platelet count (191.77–400.37 vs. 203.00–433.00 ×109/L), MPV (7.30–9.91 vs. 7.20–10.00 fL), PDW (38.09–59.83 vs. 37.10–58.50%), PCT (0.17–0.33 vs. 0.17–0.35%), PMDW (0.68–1.06 vs. 0.67–1.04 pg) for males vs. females, respectively. However, other parameters such as MPC, PCDW, MPM, and large platelet, did not show any significant differences.CONCLUSION: The reference intervals of platelet indices in the adult Indonesian population were different from previously established reference values, indicating the importance of dedicated reference interval determination with gender consideration.KEYWORDS: thrombocyte indices, platelet count, hematology reference values, blood platelet analysis